Estudo de pós cerâmicos de PbTiO3 utilizando-se o método dos precursores poliméricos - Paris, Elaine Cristina (2000)
THE STUDY OF PbTiO3 (PT) CERAMIC POWDERS USING THE POLYMERIC PRECURSOR METHOD was started by the preparation of a precursor solution of metallic cations. Citric acid was used as quelation agent and ethylene glycol as esterification and polymerization agent. This solution was submitted to thermal treatment at temperatures about 300°C for the pyrolysis of the obtained polyester. PT crystalline powders were obtained starting from amorphous precursors, varying the calcination conditions as the temperature, the time and the furnace atmosphere. The evolution of the crystallization process of the PT was accompanied by X-ray diffraction (XRD), Raman spectroscopy and infrared spectroscopy (FTIR). It was verified that the beginning of the crystallization of the PT occurs at a temperature below the Curie temperature of the material (~ 490°C). Heat treatments for one hour at 400°C yields PT crystalline and free of secondary phases. It was observed that the formation of the PT phase takes place without the formation of an intermediary carbonate phase that can occur in perovskites obtained by the polymeric precursor method. It was verified that there was no formation of pyrochlore or fluorite intermediary crystalline phase, and the only intermediary phase found was cubic PT in some calcination stages. This indicates that the polymeric precursor method provides the homogenization of the ions at the molecular level, during the synthesis process. Aiming at a better understanding of the crystallization process, a comparison was performed between the amorphous and crystalline powders by means of X-ray absorption, using EXAFS (Extended X-Ray Absorption Fine Structure) and XANES (X-Ray Absorption Near Edge Structure) spectra. It was thus verified that the amorphous powders present a short distance structure formed by sixfold oxygen titanium coordination coexisting with fivefold oxygen titanium coordination. Photoluminescent property at room temperature was detected in the amorphous powders. It was verified by reflectance spectra the presence of a tail and of optical exponential borders which are characteristic of amorphous semiconductors. It was also verified that these tail and borders are sensitive to the temperature and to the time of calcination. With the increase of the degree of crystallization of the material and the consequent ordering of the crystalline phase, this luminescent property disappears. By means of theoretical calculations it was possible to verify that the amorphous powder induces electronic levels in the area of the band gap of the material. This fact favors the recombination of the electron-hole pair, which is possibly the responsible for the photoluminescence.